Hinduism: A Perspective on the World and Life Education - Khanal, Ganesh (Rupantaran: A Multidisciplinary Journal, 2021)
Once religion was ruling the world as science is doing today. The rule is possible through power and knowledge. This indicates that religious philosophy can also regarded as an important source of power and knowledge. Hinduism, Buddhism, Christianity and so on as forms of religious faith have different philosophy become basis of knowledge. This paper, based on review of articles relevant on the theme, Hinduism, argues that Hinduism is an important perspective on knowledge which explains what world is and how it is operating. The ultimate goal of life is to get liberation which is possible through Hinduism. Hinduism has four basic paths that lead to union with God. These paths are for persons of different temperaments and natures. Some may prefer contemplation, some may be rational, some may be emotional and some may believe in action. Each path is called Yoga (Yoking of mind to God. These yoga are: (i) Raj-yoga, (ii) Jnana-yoga, (iii) Bhakti-yoga, (iv) Karma-yoga, through which human beings liberates himself/herself. Thus Hinduism is a perspective of knowledge which guides human beings understanding the nature of the world and the way through which liberation is possible.